IMPLEMENTASI NILAI-NILAI MULTIKULTURAL DI UNIVERSITAS YUDHARTA PASURUAN - M. Jamhuri (Universitas Yudharta Pasuruan, 2019)
University of Yudharta Pasuruan was established in Pasuruan East Java on 1 August 2002 based on Decree of the Minister of National Education through Directorate General of Dikti Number: 146/D/0/2002, then renewed with decree of Minister of National Education through Dirjen Dikti number: 919/D/T/2005 S. D Number: 929/D/T/2005.The multicultural theory according to Azyumardi Azra is one of the fundamental virtues of democracy, but it has an ambivalent power that is termanivestated in two forms; form of solid and democratic forms. Being tolerant is letting or allowing others to be themselves, respecting others, by appreciating their origins and background.The design that researchers use is a type of qualitative research with phenomenological design. Namely the design of research, whose plan and structure of research are made in such a way, so that can be obtained answers to questions in the study, from each individual give the answer of each case or experience they know related to the question above.Evidence of the social turmoil that is happening in Depok and Surabaya, East Java and Indonesia, such as radicalism, terrorist groups that often impose the will in instilling an idea against others, often the riot as the case happens on Tuesday at. 22. Wib, 08 may 2018, about the Perlawana and deprivation of several firearms owned by terrorist prisoner and murder of 4 police officers sadistic, and the A police officer by NAPI terrorism which took place in Rutan Mako Brimob, Kelapa Dua, Depok, West Java. And simultaneous bombardment in one day, on Sunday 13 May 2018 in three Greja in Surabaya namely: a) Greja Santa Maria, Ngagel Surabaya. b) Christian Greja Indonesia Jl. Diponegoro Surabaya. c) Greja Pantekosta Jl. Arjuno Surabaya, and the night there is another bombing in Rusunawa, Jl. Along near Polsek Taman, Sidoarjo. And the next day on May 14, 2018 there was another bombing in Surabaya. On Wednesday, 16 May 2018 there was another attack in Riau Mapolda, which is a white mubil in the police, but the motorist fought and crashed the police, and the police passed away, and the perpetrator also announced in Kompas TV was set as a terrorist. It is necessary to further increase the ideals of Romo Kyai Sholeh Bahrudin: To create a campus that is tolerant, cool, peaceful, harmonious, mutual respect for each other and respect the differences in which all of them is a manifestation of the sublime value of the attitude of multiculturalism.